2023
DOI: 10.1371/journal.pone.0284960
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and political predictors of Theory of Mind in adulthood

Abstract: Individual differences in Theory of Mind (ToM)–the ability to understand the mental states of others–are theorised to be predicted by socio-demographic and political factors. However, inconsistent findings on the relationships between various socio-demographic predictors and ToM, as well as a paucity of research on political predictors of ToM, have left a gap in the literature. Using a recently validated self-report measure of ToM in a large sample (N = 4202) we investigated the unique contributions of age, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…These findings on age and sex agree with Clutterbuck et al 's (2021) findings for the original English FIMI. The sex differences found in the present study are also in line with very recent findings of Clutterbuck et al (2023) who found that women reported higher FIMI scores than men. Moreover, controlling for sex did not change how the FIMI-G was related to the other applied measures.…”
Section: Validitysupporting
confidence: 93%
“…These findings on age and sex agree with Clutterbuck et al 's (2021) findings for the original English FIMI. The sex differences found in the present study are also in line with very recent findings of Clutterbuck et al (2023) who found that women reported higher FIMI scores than men. Moreover, controlling for sex did not change how the FIMI-G was related to the other applied measures.…”
Section: Validitysupporting
confidence: 93%